Study of Seismicity Based on the Results of Hypocenter Relocation Using Double Difference (HypoDD) Method in West Sumatera and Its Surrounding - Syafriani; Furqon Dawam Raharjo; Suaidi Ahadi; Mohamad Ramdhan (Postgraduate, University of Mataram, 2023)
The presence of the Indo-Australian plate, the Eurasian plate and the active Sumatra fault zone makes the West Sumatra region and its surroundings have very high seismic activity. To describe the seismicity pattern, it is necessary to analyze the earthquake hypocenter relocation, one of which is using the double difference (hypoDD) method. This method basically uses the data residual travel time from each hypocenter pair to the earthquake seismic station. The purpose of this research is to analyze the relocation of the hypocenter and describe the seismicity pattern in the West Sumatra and surrounding areas. The data used in this study are the time arrivals of P and S waves during the period of Â 2022 obtained from the earthquake catalog at the Padang Panjang Geophysical Station. The results showed that the earthquake hypocenter was relocated 888 out of 934 earthquake events and the distribution of hypocenter relocation produces a good seismicity pattern. From the results of the earthquake hypocenter relocation, the seismicity pattern in the West Sumatra region and its surroundings is generally influenced by subduction zones and some due to active fault zones. Seismicity in the subduction zone and active faults of Sumatra has a depth of about 50 - 250 km and 5 - 20 km. This indicates that during the period of 2022, subduction zones with medium to deep depths are very active as well as in Sumatra's active fault zones, especially Â in the Sianok segment.